Application Of The Principles Of Insurance Law In Fire Insurance Agreements On Credit Guarantees Attached Object Security Rights - Rois Harliyanto; Jawade Hafidz (Jurnal Akta, 2019)
The purpose of this study were 1) to know application of the principles of insurance law in fire insurance agreements on credit guarantees attached object security rights, 2) To know the weaknesses in the application of the principles of insurance law in fire insurance agreements on credit guarantees attached object security rights.Approximation methodused is a normative juridical research that refers to the theories, doctrines, norms, principles, rules relating to matters pertaining to insurance law. The nature of this research was analytic descriptive depict or describe the facts with the implementation of analytical and systematic.Based on this study concluded that 1) Application of the principles of insurance law in fire insurance agreements on credit guarantees attached object security rights are concerned principle consensual taken from one of the terms of agreement, namely the agreement of both parties. People can not be forced to give agreement. Agreed given by force is a contradiction interminis. Coercion indicates the absence of agreement that may be performed by other parties. The deal gives the option to the parties, to agree or disagree bound by a treaty with legal consequences. 2) A weakness in the application of the principles of insurance law in fire insurance agreements on credit guarantees attached object encumbrance is Risk Coverage and Exclusions goods insured.Keywords: Principles of Law; Insurance, Agreements; Fire; Collateral Loans; Mortgage.